Diagnosis and testing for growth hormone deficiency across the ages: a global view of the accuracy, caveats, and cut-offs for diagnosis - Yuen, Kevin C J; Johannsson, Gudmundur; Ho, Ken K Y; Miller, Bradley S; Bergada, Ignacio; Rogol, Alan D (Endocrine Connections, 2023)
Growth hormone deficiency (GHD) is a clinical syndrome that can manifest either as isolated or associated with additional pituitary hormone deficiencies. Although diminished height velocity and short stature are useful and important clinical markers to consider testing for GHD in children, the signs and symptoms of GHD are not always so apparent in adults. Quality of life and metabolic health are often impacted in patients with GHD; thus, making an accurate diagnosis is important so that appropriate growth hormone (GH) replacement therapy can be offered to these patients. Screening and testing for GHD require sound clinical judgment that follows after obtaining a complete medical history of patients with a hypothalamic–pituitary disorder and a thorough physical examination with specific features for each period of life, while targeted biochemical testing and imaging are required to confirm the diagnosis. Random measurements of serum GH levels are not recommended to screen for GHD (except in neonates) as endogenous GH secretion is episodic and pulsatile throughout the lifespan. One or more GH stimulation tests may be required, but existing methods of testing might be inaccurate, difficult to perform, and can be imprecise. Furthermore, there are multiple caveats when interpreting test results including individual patient factors, differences in peak GH cut-offs (by age and test), testing time points, and heterogeneity of GH and insulin-like growth factor 1 assays. In this article, we provide a global overview of the accuracy and cut-offs for diagnosis of GHD in children and adults and discuss the caveats in conducting and interpreting these tests.